Cryotherapy is preferable to ablative CO2 laser for the treatment of isolated actinic keratoses of the face and scalp: a randomized clinical trial3. (May 2014) - Zane, C.; Facchinetti, E.; Rossi, M.T.; Specchia, C.; Ortel, B.; Calzavara‐Pinton, P.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Actinic keratosis (AK) has the potential to progress to squamous cell carcinoma. If single or few AKs develop on normal or mildly photodamaged skin, lesion‐directed treatments are considered valuable options despite poor knowledge of their therapeutic activity. What does this study add? The rate of patients with complete remission and lesions with complete remission is similar after 3 months after both cryotherapy and CO2 laser treatment, but with cryotherapy more patients remain in stable remission after 12 months. Cryotherapy is also more effective for thick lesions.